Disbalance of testosterone is a risk factor of the beginning of ischemic stroke of middle age men - B. M. Doronin; Ye. A. Vas’kina; O. A. Denisova (Бюллетень сибирской медицины)
The aim of work is to exposure how disbalance of male sex hormones in the period of the age-specific reorganization affects development of atherosclerosis and vascular disorders by the example of ischemic stroke, establishment of correlation between hormonal dysfunction by the example testosterone and lipid metabolism according to the somatic type in the critical period of ischemic stroke. The pilot analysis of level of sex hormones by the example testosterone, lipids and body mass index confirms that there is correlation between these indices. Rising of body mass index is accompanied by reduction of sex hormone concentration, but for all that levels of cholesterol and atherogenic fraction are increased.